Incremental Forming as a Rapid Tooling Process - Afonso, Daniel; Alves de Sousa, Ricardo; Torcato, Ricardo; Pires, Liliana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the general concept and applications of rapid tooling technologies and introduces the use of incremental forming for the development of rapid sheet tools. Methods and techniques for tool design and development are discussed, considering their manufacture using incremental forming and complementary processes. The mechanical and thermal performance of sheet metal tools is analyzed. Finally, possible applications are introduced, with the description of some case study examples. .
1 Fundamentals of rapid tooling -- 1.1 Concept and classifications -- 1.2 Direct AM rapid tooling processes -- 1.3 Indirect AM rapid tooling processes -- 1.4 Other rapid tooling technologies -- References -- 2 Incremental sheet forming -- 2.1 The role of incremental sheet forming -- 2.2 Operation principle -- 2.3 Machines and tools -- 2.4 Part design and applications -- 2.5 ISF as a rapid tooling process -- References -- 3 Complementary manufacturing processes -- 3.1 Sheet metal forming processes -- 3.2 Cutting and drilling -- 3.3 Welding and joining -- 3.4 Finishing -- References -- 4 Sheet metal tools design -- 4.1 Geometric specifications -- 4.2 Mechanical behaviour -- 4.3 Thermal behaviour -- References -- 5 ISF Rapid tooling applications -- 5.1 Geometry definition and tooling pre-design -- 5.2 Composite materials processing -- 5.3 Low pressure polymer processing -- References.
Keywords: Manufactures; Building materials; Engineering design; Machines, Tools, Processes; Structural Materials; Engineering Design